O fantástico nos contos de Murilo Rubião e de Julio Cortázar: entre o mito literário e a polimetáfora - Boranelli, Valdemir (2008)
In the 19th century the fantastic literature has opened itself to its own invention and from that fact emerged arbitrariness and inconsequence. From this point on the purpose of the study is the relation between two aspects the real and the fantastic - building up the narrative action in the short stories by Murilo Rubião and their literary value. The objective of the study will be the analysis of some short stories by Murilo Rubião: A fila (1974); A noiva da casa azul (1947); Bárbara (1947); O lodo (1974); Teleco, o coelhinho (1965). The analysis of these short stories focus the main research subject: to recognize how verisimilitude works in fiction and the way metaphor and hyperbole are applied as multimetaphors, taken as a poetic work, in the light of the short stories by Julio Cortázar. We have searched some of the short stories by the Argentinian writer Julio Cortázar: Carta a una señorita en Paris (1951); Cartas de Mamá (1970); En nombre de Boby (1977); La autopista del sur (1966); Las manos que crecen (1945). Since Cortázar introduced the fantastic genre in the short story, to verify likelihood and dissimilarity among the narrative proceedings, trying to determine their viability and the results from theoretical presuppositions and to identify their validity applied to the theoretical reading of the fantastic genre. In face of these objectives we consider the challenging transparency of the fantastic like an imaginary fiction that cannot be translated except by ambiguity and for the eye s inquisitive and renewed time transposition to reality. These concernings are about the function performed by the multimetaphor from an analogical matrix elaborated between both the entities, and this fact materializes the myth being transferred to reality the myth as a multimetaphor. The corpus is analysed and described according to three of the structural features proposed by Todorov (2004): the verbal, the syntatical and the semantical matter through which a study has been done on the tropes metaphor and hyperbole those articulate as key-figures both in Murilo Rubião and Julio Cortázar s short stories. The last consideration refers to the analysis and acknowledgement of conceptions of these elements that structure the modern fantastic narrative by Murilo Rubião, producing as a result the realism of the multimetaphor as a phenomenon of language, concerning to the conception of Erdal Jordan presented in La narrativa fantástica (1998)